KAPASITAS PEMERINTAH KABUPATEN PELALAWAN DALAM PEMBANGUNAN KAWASAN TEKNOPOLITAN (STUDI PEMBANGUNAN KAWASAN PENDIDIKAN) - Astri Priyani Meiningrum; Auradian Marta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The background studies concerning regional development issues, particularly teknopolitan education area in Pelalawan District of Langgam. Attempts to find out what are the Government's efforts Pelalawan in the development of educational areas. And knowing the constraints faced by the Government of Pelalawan in the development of educational areas.This type of research is descriptive qualitative approach. The study aimed to describe the real situation on the ground to systematically and accurately related facts and research analysis unit, as well as field observations based on data (information) in particular. Methods of data collection is by interview, documentation and observation.The results of the study describes the capacity of government based on the duties and functions of each agency participating in the development process of the educational areas. In the implementation of the Regional Development Planning Agency (Bappeda) and the Technical Implementation Unit (UPT) has a big share of the manufacturing Masterplan. Efforts are being made in the development of the educational areas covering political effort and technical effort, in which the political effort made by BAPPEDA in preparing the budget to lobby parliament in budget disbursement. Technical efforts made in the process of land release and licensing of the Minister concerned. Then the constraints faced by the Government Pelalawan namely the budget and land release. That there is not enough budget for education regional development process entirely, and only the construction of the College of Technology Pelalawan (STTP) available, so that the area of education that target in 2017 have been completed, but it is still STTP is completed. Constraints land release has also become an important issue because of the slow process of land pelepaasan make the development process can not be done.Keywords:Government Capacity, Teknopolitan, Education Department